Adaptive super-twisting sliding mode control for a three-phase single-stage grid-connected differential boost inverter based photovoltaic system. (July 2017) - Pati, Akshaya K.; Sahoo, N.C.
Abstract: This paper presents an adaptive super-twisting sliding mode control (STC) along with double-loop control for voltage tracking performance of three-phase differential boost inverter and DC-link capacitor voltage regulation in grid-connected PV system. The effectiveness of the proposed control strategies are demonstrated under realistic scenarios such as variations in solar insolation, load power demand, grid voltage, and transition from grid-connected to standalone mode etc. Additional supplementary power quality control functions such as harmonic compensation, and reactive power management are also investigated with the proposed control strategy. The results are compared with conventional proportional-integral controller, and PWM sliding mode controller. The system performance is evaluated in simulation and in real-time. Highlights: An advanced adaptive super-twisting sliding mode control with the combination of double-loop control is used to track the DC-biased sinusoidal voltage of the boost inverter. An adaptive super-twisting sliding mode control is used to regulate the voltage across the DC-link capacitor. A modified control approach is used to compensate the harmonics under nonlinear load and also for reactive power management. The differential boost inverter is tested under different realistic scenario: Variation in solar insolation, dynamic load condition, sudden change of grid voltage and also transition from grid-connected to standalone mode and vice-versa. All these conditions are validated in experimentally. A wide range of PV array can be directly integrated into the grid through the boost inverter. The efficiency of this system is high as compared to the conventional two-stage grid-connected photovoltaic system.